The Efficacy of Using Subtitled Video in Teaching Reading to Indonesian English as Foreign Language (EFL) Students - Soleman Dapa Taka (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research aims at finding out the efficacy of using Subtitled Video in teaching reading especially stories to Indonesian English as Foreign Language (EFL) students. The main question of this research: Is the use of Subtitled Video effective in teaching reading stories to Indonesian EFL students?.  The research can be an addition to the persisting teaching reading of English particularly the use of the Subtitled Video.  This research was conducted at the tenth-grade students at SMA Kristen Mercusuar Kupang, an Indonesian High School. The total number of samples was 25 students. The research used a pre-experimental method with a pre-test and post-test design. The pre-test was given to find out the basic ability of the students in reading and the post-test given to find out the students’ improvement in reading after giving the treatment by using Subtitled Video as media. The findings show that using the Subtitled Video as media is effective in teaching reading to Indonesian EFL students. It is supported by the result of the significance test through SPSS 20 program that the P was 0.00.  Therefore, it is recommended to use the Subtitled Video in developing students’ competence in reading of Indonesian EFL students.